Student-student interaction in an online learning during the covid-19 pandemic - Amrullah, Amrullah; Nanzah, Zahratun (Politeknik Negeri Bali, 2022)
Despite numerous studies investigating various aspects of online learning amidst the Covid-19 pandemic, the empirical findings reporting on the student(s)-student(s) interaction in the micro-level of the language teaching-learning process is inadequately documented. Thus, this current study was in an attempt to address this void by exploring how the students interact in online learning and identifying the perception of the student about student-student interaction in online learning for effectiveness in the online learning English teaching process. Framed in a case study, 5 students of a public University in West Nusa Tenggara participating in the Teaching English for Young Learner (TEYL) course were purposefully recruited to participate in this study. The data were garnered from a series of semi-structured interviews and a 4-month virtual classroom observation and were analyzed using thematic analysis. The findings elucidate that students enjoyed their online learning interactions and they perceived that their language skills and knowledge increased significantly. The teacher was seen to have a pivotal role in facilitating students to have effective interactions by providing various activities, prepared materials, and support. Practically, this study proposes some suggestions for teachers and students on how to establish effective student-student interaction in a language online classroom.